PENTINGNYA PENDIDIKAN LINGKUNGAN SEJAK USIA DINI - ajeng Rizki Safira (JIEEC (Journal of Islamic Education for Early Childhood), 2020)
Environmental education is education that focuses on the environment as the main axis in the discussion. One of the goals of environmental education for young children is to form a caring and respectful attitude to the environment. If the attitude and character development begins early, then as they grow older they will get used to caring and respecting the environment. Providing environmental education to children is right then through habituation it will have an impact on their lives and the environment that will come to be better.